Distribution of Alcohol Related ALDH2 Genotypes among Six Ethnic Groups of Nepal - Singh, Nanda Bahadur (Journal of Institute of Science and Technology, 2015)
This paper attempts to detect alcohol related ALDH2 genotypes among six ethnic groups of Nepal. The ALDH2*2 allele is rarely found in Caucasians but readily detect in some 50 percent of the Orientals (Mongolians). Altogether 456 blood cum nail samples were collected from six ethnic groups and DNA extraction was carried out by NaI and Phenol-Chloroform methods and finally the samples were subjected to detect the distribution of ALDH2 genotype frequencies by the use of PCR-RFLP method. Allele frequencies were also calculated by the use of Hardy-Weinberg formula for analysis and interpretation. In the case of Nepalese ethnic populations, the ALDH2*2 allele frequency was found to range from the lowest (1%) in the Raute to the highest (8%) in the Gurung through the middle values found in the Chepang (2%) and the Thakali (2.7%), respectively. The prevalence of ALDH2*2 allele in the Dravidian Munda does not rule out its possible genetic admixture with either the Caucasoid or other ethnic groups. ALDH2*2 allele was totally absent in the Caucasoid Chidimar. Therefore, the ALDH2 gene allele frequency demonstrated ethnic distinction. The Chepang showed significant deviation from Hardy-Weinberg expectation. Journal of Institute of Science and Technology, 2014, 19(1): 52-56